Methodology for design assessment of terrain linear resolution of optical-electronic Earth surface observation spacecraft taking into account uncertain operational factors - V. I. Kurenkov; E. A. Pupkov (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение)
Studies have been conducted on the influence of the following uncertain operational factors on the linear resolution of spacecraft for optical-electronic observation of the Earth’s surface: deviations from the nadir of the optical axis of the spacecraft observation equipment, the wavelength in the panchromatic spectrum, and the normalized spatial frequency of optical systems. It is shown that all these factors significantly affect the terrain linear resolution index. A methodology is proposed for design assessment of terrain linear resolution, taking into account uncertain operational factors that can be used to determine the probabilistic indicators of terrain linear resolution, namely, the probability of obtaining terrain linear resolution of not less than a given value, and the value of terrain linear resolution with a given probabilistic guarantee. It is shown that the type of distribution laws of the input quantities significantly affects the resulting laws of spacecraft terrain linear resolution, obtained by calculated dependence. In the area of small probabilities, the worst values of terrain linear resolution are obtained under the normal laws of input values, and in the area of medium and high probabilities, the worst values are obtained with uniform distributions. It is shown that the values of terrain linear resolution for spacecraft with a lens optical system are better than those with a mirror optical system, all other things being equal. For real optical systems, there are limitations on the range of operating spatial frequencies transmitted by the optical system that lead to the fact that the terrain linear resolution cannot be better than pixel resolution.